2002
DOI: 10.1074/jbc.m109263200
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of the Vps34p Phosphoinositide 3-Kinase Is Necessary and Sufficient for the Interaction with the Vps15p Protein Kinase

Abstract: Vps34p is a phosphatidylinositol 3-kinase that is part of a membrane-associated complex with the Vps15p protein kinase. This kinase complex is required for the delivery of soluble proteins to the lysosomal/vacuolar compartment of eukaryotic cells. This study examined the Vps34p-Vps15p association and identified the domains within each protein that were important for this interaction. Using several different approaches, the interaction domain within Vps34p was mapped to a 28-amino acid element near its C termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 57 publications
4
38
0
Order By: Relevance
“…S1 in the supplemental material). Mutational analysis in S. cerevisiae revealed that the last amino acids of PI3-kinase are essential for kinase activity (6). On the other hand, Cterminal fusion proteins with GFP or the TAP tag have been described in the literature (24).…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). Mutational analysis in S. cerevisiae revealed that the last amino acids of PI3-kinase are essential for kinase activity (6). On the other hand, Cterminal fusion proteins with GFP or the TAP tag have been described in the literature (24).…”
Section: Discussionmentioning
confidence: 99%
“…For the rapamycin experiments, autophagy assays were performed on cells that had been treated with 0.2 g/ml rapamycin for 0, 1, or 3 h at 30°C. Western Immunoblotting and Immunoprecipitations-For the Western immunoblots, protein extracts were prepared by a glass-beading method described previously (56,57). The resulting protein extracts were separated on SDS-polyacrylamide gels and transferred to nitrocellulose membranes (Hybond ECL, Amersham Biosciences) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The Supersignal chemiluminescent substrate (Pierce) was subsequently used to illuminate the reactive bands. The carboxypeptidase Y (CPY) immunoprecipitation experiments were performed as described (57,59).…”
Section: Methodsmentioning
confidence: 99%
“…This function is conserved from yeast to human (44). For the Vps pathway, Vps34p is recruited from the cytosol to the Golgi/endosome via interaction with the membrane-associated protein kinase Vps15p, which also stimulates the phosphatidylinositol 3-kinase activity of Vps34p (48,49). The C-terminal 11 amino acids of Vps34p (amino acids 864 -875) are implicated in the protein association on the membrane (50).…”
mentioning
confidence: 99%
“…The C-terminal 11 amino acids of Vps34p (amino acids 864 -875) are implicated in the protein association on the membrane (50). Furthermore, the deletion of the C-terminal 11 residues reduces PI3K activity (49,50).…”
mentioning
confidence: 99%